Evaluation Of Cutting Force in End Milling Process of Aluminum Alloy 6061-T6 Using Tungsten Carbide Inserts with MQL Method Utilizing Hybrid Nanofluid - Wahaizad, Safiei; M. M., Rahman; A. R., Yusoff; Wajiha Tasnim, Urmi; Zetty Akhtar, Abd Malek (Akademi Baru, 2021)
As an alternative to conventional metal working fluid in the end milling process, a combination of newly developed tri-hybrid SiO2-Al2O3-ZrO2 in aqueous-based nanofluid was delivered to the cutting zone using the MQL technique. The liquid has excellent thermal-rheology properties that can offer effective cooling and lubricating during the process. The tri-hybrid nanofluid application is environmentally safe, thus promoting sustainable manufacturing compared to the conventional working fluid. In this experimental study, the cutting forces were investigated comprehensively. Tri-hybrid nanofluid presents in atomizing conditions using the minimum quantity lubricant (MQL) technique at the cutting zone. Industrial standard inserts, namely uncoated, CVD TiCN-Al2O3 and PVD TiAlTaN tungsten carbide used in the experiments. End milling process variables were cutting speed, feed rate, depth of cut, MQL flow rate and nanofluid concentrations. The response data were analyzed statistically based on the design of experiment and regression models were developed for each response according to response surface methodology. Higher cutting force was observed at extreme machining parameters, which regards to higher material removal rate. During the cutting process of Aluminum Alloy 6061-T6, the cutting force, Fr measured was between 16 Newton and 30 Newton. The cutting force in Y-axes (Fy) demonstrates a higher magnitude than others due to the cutting feed of AA6061-T6 in the Y direction. CVD TiCN-Al2O3 tungsten carbide exhibited higher cutting force (Fy) due to coated hardness and tool failures mechanism on both rake and flank face as the wear phenomenon will increase the land contact area. In summary, the resultant cutting force (Fr) was recorded below 30 Newton, indicating the significant improvement in the end milling process. For future experimental works, the cutting force can be explored by considering different nanofluids, extreme machining conditions and brittle material.